Effects of 2-methoxyestradiol, an endogenous estrogen metabolite, on SNO and WHCO3 oesophageal cancer cell growth - Joubert, Annie M. (University of Pretoria, 2013)
Dissertation (MSc (Physiology))--University of Pretoria, 2006.